(untitled) (Communications in Computational Physics, 2020)
Evaluation of possible leakage pathways of CO2 injected into geological formations for storage is essential for successful Carbon Capture and Storage (CCS). A channel in the borehole cement, which secures the borehole casing to the formation, may allow CO2 to escape. Risk assessment and remediation decisions about the presence of such channels depend on channel parameters: radial position r from the center of the borehole; channel thickness d; azimuthal position φ of the channel; and azimuthal extent θ of the channel. Current state-of-the-art cement-bond logging technology, which uses only the first arrival at a centralized borehole receiver, can diagnose limited details about CO2 leak channels. To accurately characterize the possible leak paths in the cement, we use a 3-dimensional finite-difference method to investigate the use of the abundant data collected by a modernized monopole sonic tool that contains an array of azimuthally distributed receivers. We also investigate how to improve the tool design to acquire even more useful information. For cases where borehole fluid is either water or supercritical CO2, we investigate various receiver geometries, multimodal analyses of multi-frequency data to discover the type of logging tool that provides the best information for CCS management. We find that an appropriate choice of wave modes, source frequencies, source polarities, and receiver locations and offsets provides sensitivity to d, φ, θ. The amplitude of the first arrival from a monopole source is sensitive to θ. Amplitudes at receivers at different azimuths are sensitive to φ. The slow Stoneley mode (ST2) velocity is sensitive to d, but ST2 is not easy to pick when θ and d are small. Further improvement is necessary to provide comprehensive information about possible flow channels in casing cement.